OP0077 Muscle Alterations in an Experimental Model of Chronic Arthritis. (9th June 2015) - Little, R.D.; Prieto-Potin, I.; Villalvilla, A.; Pérez-Baos, S.; Gratal, P.; Herrero-Beaumont, G.; Largo, R.
Abstract : Background: Rheumatoid arthritis (RA) is an inflammatory arthropathy with a range of additional systemic consequences. Rheumatoid cachexia (RC), the condition of decreased muscle mass with stable or increased fat mass, is one such phenomenon. Muscle atrophy in RC appears to be driven by circulating pro-inflammatory cytokines 1 . However, alterations to pro-inflammatory gene expression within muscle may also contribute to the wasting process. Objectives: Characterise alterations to muscle structure and gene expression in an animal model of chronic inflammatory arthritis. Methods: Nineteen male, New Zealand white rabbits were randomly assigned to two groups: control (n=12) and antigen-induced arthritis (AiA; n=7). Chronic arthritis was induced over six weeks via intra-dermal ovalbumin sensitization and four subsequent intra-articular injections. Nineteen gastrocnemius muscles were collected for gene expression studies and 10 tibialis anterior muscles (control n=6; AiA n=4) were collected for both gene expression and histological studies. IL-1β, IL-6, TNF, CCL-2 (MCP-1), myostatin and two atrogenes, MuRF-1 and atrogin-1, were quantified using real-time PCR. Tibialis anterior mid-belly cross-sections were stained with haematoxylin & eosin and for ATPase activity to measure whole muscle cross-sectional diameter (CSD) and type II fibre CSD, respectively. Rabbits were weighed weekly and serum CRP was measured at week 6. Group comparisons were performed using Mann-Whitney tests and associations were tested using Spearman correlation analyses. Results: AiA rabbits exhibited significantly less weight gain than controls, with a maximum cumulative difference of -160g vs. +570g (p<0.0001) and a 74-fold increase in serum CRP (p=0.0003). Tibialis anterior of AiA rabbits showed a 16% reduction in type II myofibre CSD (p=0.0159) and a 27% reduction in whole muscle CSD (p=0.0095) alongside a 11-fold increase in IL-1β (p=0.0095), a 21-fold increase in IL-6 (p=0.0381) and a 14-fold increase in CCL-2 mRNA (p=0.0095). Gastrocnemii of AiA rabbits demonstrated similar, yet less pronounced inflammatory activity with a 3-fold increase in IL-1β (p=0.0012), and a 5-fold increase in both IL-6 (p=0.0221) and CCL-2 (p=0.0018) alongside a 3-fold and 2-fold increase in the atrogenes MuRF-1 (p=0.0283) and atrogin-1 (p=0.0130), respectively. Conversely, tibialis anterior and gastrocnemius muscles of AiA rabbits expressed 78% (p=0.0095) and 70% (p=0.0097) less myostatin with no alteration in TNF mRNA. Correlation analyses revealed that tibialis anterior whole muscle CSD and type II myofibre CSD were inversely associated with the expression of pro-inflammatory, muscle-derived cytokines. Conclusions: Our model of chronic arthritis induced an RC-like state with reduced animal weight and muscle size, an up-regulation of atrogene expression, indicating muscle protein breakdown, and a parodixcal decrease in myostatin. Arthritis also up-regulated serum CRP and appeared to activate an inflammatory phenotype in skeletal muscle. We propose that inflamed muscle tissue may contribute to the process of RC via a mechanism of autocrine atrophy triggered by increased secretion of muscle-derived, pro-inflammatory mediators. References: Summers GD, Metsios GS, Stavropoulos-Kalinoglou A, Kitas GD. Rheumatoid cachexia and cardiovascular disease. Nature Publishing Group. 2010 Aug;6(8):445–51. Disclosure of Interest: None declared